HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU PEDAGANG DALAM PENGELOLAAN SAMPAH ORGANIK DI PASAR RAKYAT BEBANDEM TAHUN 2022 - Maulana, Hadi Fadli; Sudiadnyana, I Wayan; Jana, I Wayan (Jurnal Kesehatan Lingkungan (JKL), 2023)
Based on the results of initial observations at the Pasar Rakyat Bebandem, there were still piles of garbage scattered in front of the market and causing an unpleasant odor which could potential for disease. The purpose of this study was to determine the relationship between knowledge and attitudes with the behavior of traders in organic waste management at the Pasar Rakyat Bebandem. This study used an observational or non-experimental research design and uses a cross-sectional approach. The total population of traders in the Pasar Rakyat Bebandem is 458 people, while the number of samples is 82 people. The results of the study show that there is a relationship between knowledge and behavior in managing organic waste at the Pasar Rakyat Bebandem in 2022 with a P value = 0.00 and a contingency coefficient (CC) value of 0.436. Suggestions that can be given to always carry out waste management, provide counseling, and make programs related to waste management.